Heavy metal determination of brinjal cultivated in soil with wastes (Progressive Agriculture, 2017)
An experiment was conducted to determine the heavy metal status in fruits and roots of brinjal plant cultivated in soil mixed with wastes at Environmental Science Field Laboratory, Bangladesh Agriculture University, Mymensingh. Two brinajl varieties of BARI namely BARI1 and BARI4 and three treatments viz. T0: control soil, T1: Municipal waste and T2: Industrial wastes were used for the present study. The data were collected on Cu, Zn, Pb and Fe of both fruits and roots of the brinjal plants. The data were analyzed by Atomic Absorption Spectrophotometer (AAS). The two factors experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Results revealed that the initial contents of Cu, Zn, Pb and Fe were higher in industrial waste mixed soil as compared to municipal waste and control soil. In contrast, the incidence of heavy metals in fruits and roots were tolerable range in normal and municipal waste mixed soil while industrial waste mixed soil showed highest values. This study also showed that the industrial waste treated plants of BARI1 uptaked the more Cu and Zn content (16.12 and 21.39 mg/kg, respectively) in roots while plants of BARI4 gave the more Pb and Fe content (0.363 and 365.70 mg/kg, respectively) in roots compared other interaction treatments. However, without waste treated or normal soil showed lowest effect on the incidence of heavy metal but municipal waste obtained the moderate effect. This result revealed that the both control and municipal waste treated soil may be acceptable for the cultivation of BARI brinjal in Bangladesh condition. This study also suggested that the industrial waste treated soil may not suitable for the vegetable cultivation might be due to the higher incidence of heavy metal in fruits and roots.Progressive Agriculture 27 (4): 453-465, 2016